Revision of the South American stiletto fly genera Entesia Oldroyd and Melanothereva Malloch, with the description of a new genus (Therevidae: Agapophytinae) - Winterton, Shaun L.; Irwin, Michael E. (Zootaxa, 2023)
The South American members of the stiletto fly subfamily Agapophytinae (Diptera: Therevidae) occur in the South American Transition Zone, predominantly in Chile and southwestern Argentina. The four agapophytine genera described from this region are Entesia Oldroyd, 1968; Melanothereva Malloch 1932; Pachyrrhiza Philippi, 1865; and more recently, Sigalopella Irwin & Winterton, 2020. Here we revise Melanothereva and Entesia and describe the new monotypic genus Pachylopella. Keys to South American Agapophytinae genera and species of Melanothereva and Entesia are provided.